Melting and re-entrant melting of polydisperse hard disks - Ruiz, Sampedro Pablo (2020)
Because of long-wavelength fluctuations, the nature of solids and phase transitions in 2D are different from those in 3D systems, and have been heavily debated in past decades, in which the focus was on the existence of hexatic phase. Here, by using large scale computer simulations, we investigate the melting transition in 2D systems of polydisperse hard disks. We find that, with increasing the particle size polydispersity, the melting transition can be qualitatively changed from the recently proposed two-stage process to the Kosterlitz-Thouless-Halperin-Nelson-Young scenario with significantly enlarged stability range for hexatic phase. Moreover, re-entrant melting transitions are found in high density systems of polydisperse hard disks, which were proven impossible in 3D polydisperse hard-sphere systems. These suggest a new fundamental difference between phase transitions in polydisperse systems in 2D and 3D.